Advantages of using nanomodified polypropylene mesh in the surgical treatment of postoperative large abdominal hernia - Lutkovskyi, Ruslan (Journal of Education, Health and Sport, 2022)
Surgical treatment of large postoperative abdominal hernias (PAH) with the use of classic techniques of allogeneoplasty (sublay, onlay) is often accompanied by an increase in intra-abdominal pressure (IAP) and a decrease in the volume of the abdominal cavity, which in the postoperative period leads to abdominal compartment syndrome (ACS). 2.4 - 3.6% of cases and mortality in 1.2 - 3.4% of observations [1, 2]. This requires a special method of closing a large defect of the abdominal wall, which would not increase IAP. The use of the method of dividing the anatomical components of the anterior abdominal wall according to the modified technique of Ramirez operation in combination with sublay alloplasty contributes to the creation of the optimal volume of the abdominal cavity and improves the results of treatment, in particular, the frequency of ACS decreases [3, 4, 5]. However, the use of a combined operation with a classic polypropylene mesh leads to a high frequency of complications from the postoperative wound, such as seroma (30.8 - 60.4%), suppuration of the postoperative wound (4.8 - 6.4%), ligature fistula (1 .2 - 3.0%), meshoma (0.06 - 1.60%) [6, 7]. One of the causes of postoperative wound complications is the development of aseptic inflammation of the tissues of the abdominal wall as a result of their contact with the classic polypropylene mesh. Long-term aseptic inflammation of the subcutaneous base, muscles, aponeurosis, and fascia inhibits the process of germination of the polypropylene mesh by the connective tissue, which leads to its shrinkage, and in the case of infection, to the migration of the mesh and recurrence of the hernia. In our opinion, the use of a modified polypropylene mesh with an antiseptic of polyhexamethyleneguanidine chloride and carbon nanotubes in combination with a modified technique of the Ramirez operation will make it possible to improve the results of operative treatment of PAH. Aim – to improve the results of surgical treatment of large postoperative abdominal hernias (PAH) by using a modified technique of the Ramirez operation in combination with «sublay» alloplasty using a modified polypropylene mesh. Materials and methods. An analysis of the surgical treatment of 164 patients with large-sized PAH was performed. Depending on the type of mesh implant used during operative treatment, the patients were divided into two groups. In 82 (50%) patients of group I, surgery was performed according to the modified Ramirez technique in combination with «sublay» alloplasty using a modified polypropylene mesh, in group II, 82 (50%) patients underwent surgery according to the modified Ramirez technique in combination with «sublay alloplasty using classic polypropylene mesh. Results and discussion. Statistically significantly better results were obtained in patients of group I compared to group II. The duration of inpatient treatment in group I was (7.0±1.0) days, in group II – (12.0±2.2) days. Conclusion. Operative treatment of large PAH using the modified technique of the Ramirez operation, combined with the «sublay» technique using the modified polypropylene mesh, is much more effective compared to the use of the classic polypropylene mesh, which was evidenced by a decrease in the frequency of postoperative complications.